KEDUDUKAN IWAD TERHADAP KEABSAHAN KHULUK : (Studi Komparatif Pendapat Imam Malik dan Imam Syafi’i) - Hidayat, Taufiq; Panji Maulana, Rahmatulloh (Prodi Ahwal al-Syakhsiyah STAI Darussalam Nganjuk, 2022)
Iwad is a ransom property or compensation given to a husband to divorce his wife. Imam Shafi'i argues that iwad is one of the pillars that cannot be abandoned and affects the validity of khuluk. On the other hand, Imam Malik considers that khuluk performed without iwad is still valid. This type of research is library research through a qualitative approach. Analyzed using the descriptive-analytical method and comparative analysis method. As for the results of this research: according to Imam Malik, khuluk may occur without iwad because khuluk is a form of breaking up a marriage like a divorce. Meanwhile, Imam Shafi'i views iwad as an urgent and core part of khuluk, because without Iwad, khuluk will not occur. The urgency of iwad refers to the opinion of Imam Shafi'i who emphasizes in the khuluk lafadz it must be clearly stated the number and type of goods used as ransom property. The method of determining the law used by Imam Malik is more focused on the pattern of determining the law based on the text of al-Bayan bil Qaul, namely an explanation through the hadith of the Prophet or the word of Allah SWT. Meanwhile, Imam Shafi'i, apart from referring to the Qur'an and hadith, Imam Shafi'i also uses qiyas. In this case, it is analogous to the ransom property with buying and selling assets.